Developing Language Games to Teach Speaking Skill For Indonesian Senior High School Learners - Amrullah, Ahmad Zubaidi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2015)
This research aims at developing language games to teach speaking for the students joining English Study club as extra-curricular program at one of the State Islamic Senior High Schools in Gresik, Indonesia. It tries to develop the suitable speaking games and to investigate the students‘ responses toward the developed games. This research and development (R&D) is conducted by adapting Thiagarajan‘s (1974) model called 4D which consists of Defining, Designing, Developing, and Disseminating. The data were gained through interview and questionnaire, and observation checklist. The interview is conducted to study the frontend, specifying instructional objectives, and learner analysis. The questionnaire is employed to do task-concept analysis, to get the students‘ responses, and to submit the experts‘ appraisal. Meanwhile, the checklist is used to conduct development testing. Finally, the product of the study is in the form of a handbook entitled ―A Library of Games‖ which comprises 3 units and 50 kinds of games for teaching speaking skill.